(untitled) (Academia Science Repository, 2023)
Purpose of study: to assess how aging and comorbidities affect outcomes in patients who underwent surgery for colorectal cancer (CRC) treatment, specifically looking at the impact of age, sex, and comorbidities on length of stay, readmission rates, reoperation rates, and overall survival. The study aimed to identify risk factors for adverse outcomes in older patients with CRC and provide insights into appropriate perioperative management strategies to improve surgical outcomes in this population. Methods of study: The incidence of surgical interventions in elderly patients with concomitant chronic conditions has been increasing. As such, this study aimed to assess how aging and comorbidities affect outcomes in patients who underwent surgery for colorectal cancer (CRC) treatment in the Samarkand State Medical University, multidisciplinary clinic-1. This retrospective cohort study involved patients aged 40 and above who underwent elective or urgent CRC surgical resection between January 2021 and December 2022. The study analyzed independent variables such as age, sex, and comorbidities, as well as variables associated with the surgical procedure, such as stoma creation, hospitalization history, surgical approach, American Society of Anesthesiologists (ASA) score, and Charlson Comorbidity Index score. A total of 96 patients with CRC underwent surgical resection.